2021
DOI: 10.1097/rmr.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art MR Enterography Technique

Abstract: Magnetic resonance enterography (MRE) is a well-established imaging technique that is commonly used for evaluating bowel disease. While MRE can be used to assess a number of bowel conditions, the most common reason to perform MRE is for the diagnosis, surveillance and detection of complications of inflammatory bowel disease (IBD) (Table 1) (3-10). MRE has several significant advantages over CT enterography (CTE) and traditional barium-based fluoroscopic exams (i.e. small bowel series and enteroclysis) in evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 46 publications
(51 reference statements)
0
35
0
2
Order By: Relevance
“…One may further argue that MRE focuses on small bowel, and so optimization of colonic image quality is not required because the colon is not the target organ of evaluation. However, our findings suggest that colonic contents frequently degrade MRE images, which may be of concern for patients undergoing MRE have concern for IBD which affects mainly the colon 13 . Furthermore, Crohn's disease is known to affect the colon in approximately 26% of patients and in up to 56% of pediatric patients with penetrating disease 14 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…One may further argue that MRE focuses on small bowel, and so optimization of colonic image quality is not required because the colon is not the target organ of evaluation. However, our findings suggest that colonic contents frequently degrade MRE images, which may be of concern for patients undergoing MRE have concern for IBD which affects mainly the colon 13 . Furthermore, Crohn's disease is known to affect the colon in approximately 26% of patients and in up to 56% of pediatric patients with penetrating disease 14 .…”
Section: Discussionmentioning
confidence: 79%
“…However, our findings suggest that colonic contents frequently degrade MRE images, which may be of concern for patients undergoing MRE have concern for IBD which affects mainly the colon. 13 Furthermore, Crohn's disease is known to affect the colon in approximately 26% of patients and in up to 56% of pediatric patients with penetrating disease. 14 As such, our findings suggest that further study is warranted to assess methods to minimize confusing colonic contents prior to MRE.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of concern for patients undergoing MRE who have IBD, which primarily affects the colon. 8 Zhang et al 7 also reported that air-containing bowel in the colon compromised the bowel wall visualization in small bowel regions, particularly in children, which is contrary to the findings from Sinha et al 6 Moreover, Crohn's disease affects the colon of 56% of pediatric patients compared to 23% of adult patients with penetrating disease. 9 Thus, to minimize image misinterpretations based on colon content, Zhang et al suggest that bowel cleansing may be appropriate prior to MRE for patients where colonic involvement might be of concern.…”
mentioning
confidence: 94%
“…Their findings suggest that the contents of the colon led to poor bowel wall enhancement visualization using MRE, more frequently in the colon. This may be of concern for patients undergoing MRE who have IBD, which primarily affects the colon 8 . Zhang et al 7 also reported that air‐containing bowel in the colon compromised the bowel wall visualization in small bowel regions, particularly in children, which is contrary to the findings from Sinha et al 6 Moreover, Crohn's disease affects the colon of 56% of pediatric patients compared to 23% of adult patients with penetrating disease 9 .…”
mentioning
confidence: 97%
“…In addition, it can detect the complications of CD, and typically does not require anesthesia in children over 5 years of age (13).…”
mentioning
confidence: 99%